دور الجودة الشاملة في تنمية الموارد البشرية في القطاع الخاص - فروانة, حازم; ماضي, إسماعيل (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة إلى التعرف على أهمية تنمية المورد البشري، باعتباره رأس المال البشري للمؤسسات.و الكشف عن دور وأهمية كل من توظيف الموارد البشرية، وتدريبها، وتخطيط مسارها الوظيفي، وتقييم أداءها.مع بيان أهمية اكتساب الشركة لتحقيق الجودة الشاملة، وإبراز دور التنمية والتدريب في تحقيقها.والتعرف على مساهمة تنمية الموارد البشرية لشركة الاتصالات الفلسطينية في زيادة إنتاجها وتحقيق الجودة الشاملة لها. يتضح من خلال المتغير المستقل (تنمية الموارد البشرية)أن جميع متوسطات المحاور المختلفة كانت متقاربة من حيث أوزانها النسبية، أما الدرجة الكلية للإستبانة ككل فقد حصلت على وزن نسبي قدره (81.00%) مما يدلل على موافقة عينة الدراسة على دور تنمية الموارد البشرية في تحقيق الجودة الشاملة في شركة الاتصالات الفلسطينية. أن المتوسط الحسابي لدور العاملين نحو تحقيق الجودة الشاملة حصل على وزن نسبي قدره (79.00%) أي بدرجة تقدير كبيرة. مما يدلل على موافقة عينة الدراسة على دور تنمية الموارد البشرية في تحقيق الجودة الشاملة. The study aimed to identify the importance of human resource development, as the human capital of the institutions. The role and importance of human resources recruitment, training, career planning and performance evaluation. And recognize the contribution of human resources development to the Palestinian Telecommunication Company in increasing its production and achieving its overall quality. It is clear through the independent variable (human resource development) that all the averages of the different axes were close in terms of their relative weights. The overall score of the questionnaire as a whole obtained a relative weight of (81.00%). Total Quality in Palestine Telecommunications Company. The arithmetical mean of the role of workers towards achieving total quality obtained a relative weight of (79.00%), ie, with a high degree of appreciation. Which is evidence of the approval of the sample of the study on the role of human resources development in the achievement of total quality.
the role of total quality in the development of human resources in the private sector
مقال
Keywords: تنمية الموارد البشرية، الموارد البشرية، الجودة الشاملة، شركة الاتصالات الفلسطينية، الإنتاجية.; Human Resource Development, Human Resources, Total Quality, Palestinian Telecommunications Company, Productivity